(untitled) (Studia Prawnicze / The Legal Studies, 2023)
Autor artykułu podejmuje się wyzwania przedstawienia zagadnienia winy na gruncie angielskiego prawa karnego. Przedstawia rys historyczny uregulowań dotyczących rozwoju angielskiego prawa karnego i dzieli go na trzy etapy: od najazdów nordyckich w V wieku do połowy XII wieku, drugi obejmujący okres od połowy XII do drugiej ćwierci XIX wieku, który kwalifikuje jako okres kształtowania się angielskiego prawa karnego oraz trzeci etap, współczesny od połowy XIX wieku do chwili obecnej. Autor opisuje kształtowanie się zasady winy na przestrzeni wieków oraz stara się wskazać kierunek, w którym regulacje dot. zasady winy zmierzają. The author of this article takes up the challenge of presenting the issue of guilt under English criminal law. He provides a historical outline of the regulation of the development of English criminal law and divides it into three stages: from the Norse invasions in the fifth century to the middle of the twelfth century, the second covering the period from the middle of the twelfth century to the second quarter of the nineteenth century, which he qualifies as the formative period of English criminal law, and the third stage, the contemporary one from the middle of the nineteenth century to the present. The author describes the formation of the principle of guilt over the centuries and tries to indicate the direction in which the regulation of the principle of guilt is heading.